Hiding Secrets in Programs: Technical Perspective. - Wichs, Daniel (Communications of the ACM, 2024)
The article focuses on the research behind hiding secrets within computer programs, also known as program obfuscation. The author discusses how program obfuscation could revolutionize cryptography, examines how it could impact reverse engineering with a proposed virtual black box (VBB), and explores the alternate security of so-called indistinguishability obfuscation (iO)